PANDANGAN SYI’AH TENTANG SAHABAT NABI SAW - M. Kholid Muslih (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2013)
The following article tries to describe the Twelve Imams’s view about the Prophet’s Companions, quoted from their trusted views. The discussion begins by describing the views of the Companions of Ahlus Sunnah scholar, followed by a view of classic and contemporary Shi’ah Scholar, and ended by a critical analize on Shi’ah sholars’ arguments. This paper is raised as the important position of the Companions in scholarly Ahlus Sunna, because they are the main connectors between the Prophet Muhammad (PBU) with his ummah. In addition, this paper is an answer for the rejection or denial of Shi’ah to the Companions’ narrations. The study results of this paper showed that a majority of the Shi’ah scholars, both classical and contemporary, have a negative view towards Companions. This negative view is the implication of the extreme concept of Imamat, which not based on strong arguments from the Qur’an, Sunnah, and ijma ‘ulama; thus making it weak.